An Empirical Study of the Factors Relating Field Failures and Dependencies - Zimmermann, Tom; Nagappan, Nachi; Williams, Laurie; Herzig, Kim; Premraj, Rahul (Proceedings of the 4th International Conference on Software Testing, Verification and Validation (ICST), 2011)
Changing source code in large software systems is complex and requires a good understanding of dependencies between software components. Modification to components with little regard to dependencies may increase have an adverse impact on the quality of the latter, i.e., increase their risk to fail. We conduct an empirical study to understand the relationship between the quality of components and the characteristics of their dependencies such as their frequency of change, their complexity, number of past failures and like. Our study has been conducted on two large software systems: Microsoft VISTA and ECLIPSE. Our results show that components that have outgoing dependencies to components with higher object-oriented complexity tend to have fewer field failures for VISTA, but the opposite relation holds for ECLIPSE. Likewise, other notable observations have been made through our study that (a) confirm that certain characteristics of components increase the risk of their dependencies to fail and (b) some of the characteristics are project-specif while some were also found to be common. We expect that such results can leveraged for use to provide new directions for research in defect prediction, test prioritization and related research fields that utilize code dependencies in their empirical analysis. Additionally, these results provide insights to engineers on the potential reliability impacts of new component dependencies based upon the characteristics of the component.